2019
DOI: 10.1038/s41598-019-47358-3
|View full text |Cite
|
Sign up to set email alerts
|

Multicentre evaluation of Xpert MTB/RIF assay in detecting urinary tract tuberculosis with urine samples

Abstract: Genitourinary tuberculosis (GUTB) accounts for up to 40% of extrapulmonary tuberculosis cases. Rapid tests for GUTB are urgently needed because it is often associated with delayed health-care seeking, leading to serious consequences. This study evaluated the performance of the Xpert MTB/RIF assay in the rapid diagnosis of urinary tract tuberculosis (UTB) and rifampicin-resistant tuberculosis with urine specimens. In all, 302 patients were included from four hospitals in China. Suspected UTB patients were teste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 24 publications
1
11
0
3
Order By: Relevance
“…Studies have shown that pleural biopsies, obtained under medical thoracoscopy guidance, are better specimens than the pleural fluid for diagnosing tuberculous pleuritis [9,14,15]. Our group has previously evaluated the performance of Xpert using urine specimens for the rapid diagnosis of urinary tract TB, and the data indicated a better performance of Xpert than that of smear and culture identification, thus suggesting that Xpert could be considered for the diagnosis of urinary tract TB [16].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that pleural biopsies, obtained under medical thoracoscopy guidance, are better specimens than the pleural fluid for diagnosing tuberculous pleuritis [9,14,15]. Our group has previously evaluated the performance of Xpert using urine specimens for the rapid diagnosis of urinary tract TB, and the data indicated a better performance of Xpert than that of smear and culture identification, thus suggesting that Xpert could be considered for the diagnosis of urinary tract TB [16].…”
Section: Introductionmentioning
confidence: 99%
“…En torno a los datos de este estudio se observa una mayor frecuencia de lumbalgia, lumbalgia de esfuerzo y gonartrosis en ambos sexos asociada al sobrepeso y obesidad. Estudios en poblaciones cercanas muestran prevalencias similares, donde las mujeres con un alto porcentaje de grasa corporal tienen mayor probabilidad de padecer dolor lumbar severo contrastando con hombres con porcentaje de grasa menor que tienen menos riesgo 9 y hasta es considerado un factor de riesgo laboral 10 . también se confirma que el factor de riesgo que más se relacionó a problemas articulares de rodilla fue un aumento del índice de masa corporal 8 ; en Perú, la lumbalgia y sexo femenino fueron asociados en la aparición y progresión de la gonartrosis 11 .…”
Section: Discussionunclassified
“…The number of samples evaluated in each study ranged from 21 to 302, with a median value of 96. Overall, eight (67%) studies were carried out in high-burden TB countries, where the TB prevalence was 63-267 per 100 000 population (Chen et al, 2019;Jing et al, 2017;Khan et al, 2018;Kim et al, 2015;Li et al, 2017;Pang et al, 2017;Samuel et al, 2018;Sharma et al, 2014). Four (33%) studies were conducted in low-burden TB countries, where the TB incidence was 0.81-7.5 per 100 000 population (Habous et al, 2019;Hillemann et al, 2011;Mazzola et al, 2016;Tortoli et al, 2012).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%